Raising the bar for occupational health management in construction. Issue 4 (1st August 2019) - Jones, Wendy; Gibb, Alistair; Haslam, Roger; Armstrong, Jennie
Abstract : Construction-related ill health, including respiratory conditions, hand−arm vibration syndrome, musculoskeletal disorders and stress-related issues, has enormous personal and financial cost. Following research on major construction projects, a range of interventions are proposed in this paper, illustrated by examples from the Thames Tideway Tunnel project in London, UK. A consistent approach to occupational health management and health surveillance is needed across construction, with a commitment to better training and improved portability of occupational health data. Major projects are critical to raising health management standards, but good practices need to be universally adopted in small- to medium-sized enterprises to achieve lasting improvement.